Sistem Pakar Diagnosis Penyakit Sapi Ternak Potong Menggunakan Metode Naive Bayes - Certainty Factor - Dhimas Tungga Satya; Nurul Hidayat; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The low ability of domestic farms to fulfill necessity of beef and cow's milk is caused by many things. One of them is a disease. Such as anthrax, snore of cow disease, brucellosis and diseases caused by parasitic gastrointestinal worms which are the most agent of decreasing levels of beef and dairy production by breeders. Currently expert resources in diagnosing cattle diseases are limited, it takes an expert system that can replace the role of experts in diagnosing diseases in cattle. In this study to implement the expert system diagnosis of cattle disease using method Naive Bayes - Certainty Factor. Using the Naive Bayes - Certainty Factor method results in accurate and accurate diagnostic accuracy, since the output produced by the system has a level of accuracy of 92% and the system created has a user satisfaction level of 3.19411.